Metrical Fixed Point Results on \lowercase{b}-multiplicative metric spaces employing binary relaion (European Journal of Pure and Applied Mathematics, 2023)
In this manuscrit, we establish some results on the existence and uniqueness of fixed points by using b-multiplicative metric spaces(MMS) endowed with a binary relation. we also find result on the coincidence of points involving a pair of mappings. Finally some examples are presented to illustrate the suitability of our results.
Keywords: Multiplicative metric space; binary relation; relation theoretic contractions